Depiction of Shiva and Parvati on the Kanthi - Mumbai Archive Project Team (Jio Institute, 2024)
The Koli man is wearing a kanthi featuring Lord Shiva and his consort, Goddess Parvati. Both women and men wear the kanthi only on special occasions. This particular kanthi was inherited from his mother.